The world's view of the Corona pandemic and the way to deal with it - Chandoul, Amara Saad; Zughir, Widad Ali (Journal of Humanities & Social Sciences, 2021)
In this paper, the researcher stresses that the crisis of Corona, which the world has gone through and is still primarily a crisis of awareness in providing priorities. This predicts the emergence of serious economic and social problems that may afflict existing societies and systems, or arrange them in a worse way, as the foundations of justice in the world are broken.The researcher notes that the world around the pandemic is divided into three parts :The first part, whoever claims to be a true pandemic is a caution, and they are in two directions :The first one is for whoever thinks that the pandemic is natural and requires cooperation in finding a solution and complying with the provisions of the World Health Organization.The second concern whoever goes on to say that the pandemic is an effective act, and he has all the information about it and has to disclose and stop spreading it to protect humanity.The second part cover people who deny the seriousness of the pandemic and that it is just a conspiracy in preparation for the adoption of a new political system that rules the world, increases the servitude of the people and oppresses the poor, and they are in two directions:The first one, concern people who deny the existence of such a virus in the first place.The second, includes who acknowledges his existence and excludes his danger.The third part, is the part of persons holding that the existence of a pandemic or does not matter as much as it matters how to deal with it and with similar counterparts that are not literally dangerous to it, and the originality of their duty is to seek the assistance of the qualified and specialized, to provide the most important on the important and to present alternatives that prove sustainability as possible and possible. This is because the boasting of building hospitals in a short period was not accompanied by building laboratories to eradicate such a scourge and others that we live in and may be experienced by humanity in the future.The research concluded that it is necessary to not look into the existence or absence of the pandemic, but rather to look at how to deal with it and overcome it and its counterparts, without stopping people's lives or political exploitation of the crisis. It deals also to be careful in order that fear does not dominate us at the point of illusion, and to look with insight into what can carry conspiracy.The researcher adopted the inductive approach, by tracking people's opinions about COVID-19. The research also dealt with the descriptive approach, in presenting these opinions, in analyzing and clarifying their evidence, clarifying what is in, and discussing it.
Keywords: covid 19; conspiracy; world order